The thematic dimensions of the terms information and documentation in the business environment of Brazilian startups - Pinheiro dos Santos, Beatriz Rosa [UNESP]; Martins Damian, Ieda Pelogia (Ibersid Network, 2020)
An analysis is offered of the most valued dimensions of the information and documentation resources by Brazilian startups. The methodology was exploratory, using a questionnaire as an instrument for data collection and the Bardin's content analysis method (2010) for analyzing the data. The results showed three groups of divergences about what startups understood by information and documentation in their workplace. In general, it was perceived that these resources are not being administered and given enough relevance for the development of the functions that occur in these organizational environments.
Keywords: Information; Documentation; Startups; Business information and documentation; Content analysis; Brazil